GUILT TRIPPING IN AGATHA CHRISTIE’S THE MURDER OF ROGER ACKROYD - Widyani, Erika; Ekalestari, Susi (JOURNAL OF LANGUAGE, 2025)
This study examines the use of guilt-tripping as a form of psychological manipulation in Agatha Christie’s The Murder of Roger Ackroyd. The analysis centers on identifying both the causes and the types of guilt-tripping enacted by the novel’s manipulative character. Employing McPhillips’ (2022) theoretical framework on manipulative behavior, the research adopts a descriptive qualitative approach, with a focus on character and narrative analysis. The findings reveal that the primary motivations for guilt-tripping include emotional dependency, a desire to manipulate and control others, and underlying feelings of low self-esteem and insecurity. In addition, two specific types of guilt-tripping behaviors are identified: love bombing and direct guilt inducement. These manipulative strategies are not only critical to the progression of the plot but also offer deeper insight into the psychological construction of the characters. The study contributes to the field of literary psychological criticism by illustrating how emotional manipulation is intricately embedded in the structure of detective fiction.